Territorial Identities in Action - ILOVAN, Oana-Ramona (2021)
Collection Constructing Territorial Identities. Theory and Practiceis coordinated by dr. Oana-Ramona Ilovan The collection appears under the aegis of theTerritorial Identities and Development Research Centre,Faculty of Geography, Babeş-Bolyai University, Cluj-Napoca, RomaniaThis collective volume contributes to the academic literature on thetopic of territorial identity, providing professors, researchers andstudents with theoretical, methodological and applicative insights.Territorial identity is conceived as a social construct, undergoingconstant changes, being influenced by a variety of physical andhuman factors (cf. Banini, Ilovan, 2021a, 2021b; Paasi, 2021).